2017
DOI: 10.3892/ol.2017.6990
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of microRNA‑301a inhibited proliferation, migration and invasion of non‑small cell lung cancer by directly targeting DLC1

Abstract: Abstract. Increasing evidence has indicated that the abnormal expression of microRNAs contributes to tumorigenesis and tumor development. Understanding the roles of microRNAs in non-small cell lung cancer (NSCLC) might provide valuable information for therapeutic strategies in the therapy for patients with NSCLC. In the present study, significant upregulation of microRNA (miR)-301a was observed in NSCLC tissues and cell lines compared with normal adjacent tissues and a normal human bronchial epithelial cell li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
(47 reference statements)
0
6
0
Order By: Relevance
“…A research demonstrated miR-301b to stimulate cell invasion and facilitate drug resistance in pancreatic carcinoma [34]. Moreover, silencing of miR-301a could suppress cell proliferation, migration, and invasion in NSCLC, which implied to the functionality of miR-301a as a potential therapeutic strategy in NSCLC treatment [35]. Previous studies have proven that excised miR-301b could consequently inhibit bladder cancer cell proliferation, migration, and invasion [36].…”
Section: Discussionmentioning
confidence: 99%
“…A research demonstrated miR-301b to stimulate cell invasion and facilitate drug resistance in pancreatic carcinoma [34]. Moreover, silencing of miR-301a could suppress cell proliferation, migration, and invasion in NSCLC, which implied to the functionality of miR-301a as a potential therapeutic strategy in NSCLC treatment [35]. Previous studies have proven that excised miR-301b could consequently inhibit bladder cancer cell proliferation, migration, and invasion [36].…”
Section: Discussionmentioning
confidence: 99%
“…The overexpression of PRDM13 upregulates DLC1 and then inhibits proliferation and invasion of U87 cells (Zhang et al, ). Downregulation of miR‑301a and miR‐483‐3p directly targets DLC1, which inhibits the proliferation of NSCLC and CRC (Wu, Li, & Zhang, ). Besides, two signaling pathways can mediate cancer cell proliferation by DLC1, one is the Wnt/β‐catenin signaling pathway.…”
Section: The Function and Signal Pathways Dlc1 Involvesmentioning
confidence: 99%
“…DLC1, interacting with CAV‐1 (B. Yang et al, ), FK506 binding protein 51 (FKBP51) (Takaoka, Ito, Miki, & Nakanishi, ), EF1A1 (Zhong et al, ) and S100A10 (Yang et al, ), promotes RhoA and ROCK activation and then controls cell migration and invasion (Yang et al, ). Besides, DLC1 is directly targeted by downregulation of exosomal miR‐141‐3p, miR‑301a and miR‐106b to inhibit cancer cell migration in prostate cancer, NSCLC and CRC (Wu et al, ; Ye et al, ; Zhang et al, ). Phosphorylation also modulates DLC1 activity, which conversely regulates the small GTPases, Rac1 and RhoA spatiotemporal activation, thus initiates the growth‐factor‐induced directed cell migration (Cao et al, ).…”
Section: The Function and Signal Pathways Dlc1 Involvesmentioning
confidence: 99%
“…miR-146 also plays regulatory roles in the NF-κB pathway, as it negatively regulates the protein levels of IL-1 receptor-associated kinase 1 (IRAK1) and TNF receptor-associated factor 6 (TRAF6) (29,30). miRNA-301a, which is located on chromosome 17q22, has been shown to be upregulated in a number of types of cancer, including hepatocellular carcinoma, pancreatic cancer, small cell lung cancer and breast cancer, which indicates a potential role for miRNA-301a in cancer development (31)(32)(33)(34). In GC, Wang et al (35) reported that the high expression of miRNA-301a was associated with GC cell proliferation and invasion by targeting Runt-related transcription factor 3 (RUNX3).…”
Section: Introductionmentioning
confidence: 99%